Taxonomic and molecular identification of Verpa bohemica: A newly explored fungi from Rajouri (J&K), India - Anand, Nidhi; Chowdhry, P N (Recent Research in Science and Technology, 2013)
A species of mushroom, Verpa bohemica was collected from lower Shivalik range of moist temperate Conifer forest of Rajouri and identified on the basis of morphological and molecular characterization. Universal fungus primers (ITS1 and ITS4) were used in amplification process of target region of rDNA (ITS1 5.8S I). Bioinformatics approach was followed for its molecular identification. Its rDNA sequence, when aligned in GenBank by performing BLAST, matches 100% with Verpa bohemica. The rDNA sequence of this species forms a distinct clade from the rest of species of the same genus. This species is being reported and explored first time from Rajouri Dist. of Jammu & Kashmir, India.